2010
DOI: 10.1177/0019556120100408
|View full text |Cite
|
Sign up to set email alerts
|

Decentralised Planning Process in Andhra Pradesh–A late Starter

Abstract: and Karnataka is lagging behind in activating the decentralized planning process. Although AP Government has passed Conformity Act as soon as 7J'd Constitutional Amendment Act was enacted, most of the provisions of the Andhra Pradesh Conformity Act have not been made into concrete reality even today i.e., more than after a decade and half of decentralization experience in Andhra Pradesh.The functional devolution states of Andhra Pradesh as compared to some of the well performing states make it clear that AP ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In this way ensuring supportive supervision and other support on time would be possible (Tyagi, 2016). Furthermore, optimum utilization of allocated resources and collection of resources locally could be possible which will reduce the financial dependency on the state (Bray, 2003; Reddy and Bhavani, 2012). In a study of the World Bank, Uemura has listed several ways through which a community can contribute to the delivery of education such as ensuring enrollment, students daily attendance, collecting resources locally, developing infrastructure, recruiting teachers, monitoring teachers attendance and performance, helping children in the study, promoting girls education, and improving the school environment (Uemura, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way ensuring supportive supervision and other support on time would be possible (Tyagi, 2016). Furthermore, optimum utilization of allocated resources and collection of resources locally could be possible which will reduce the financial dependency on the state (Bray, 2003; Reddy and Bhavani, 2012). In a study of the World Bank, Uemura has listed several ways through which a community can contribute to the delivery of education such as ensuring enrollment, students daily attendance, collecting resources locally, developing infrastructure, recruiting teachers, monitoring teachers attendance and performance, helping children in the study, promoting girls education, and improving the school environment (Uemura, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although community participation in elementary education is a complex phenomenon, hence accomplishing it to a desirable magnitude requires strategic and consistent intervention. Several studies have revealed various barriers to community participation such as lack of resources, social power dynamics, local politics, bureaucratic power, lack of skills and knowledge, corruption, disproportionally devolution of authority and responsibility, and lack of political commitment (Acharya, 2002; Mukundan and Bray, 2004; Ramachandran, 2001; Reddy and Bhavani, 2012; Wankhede and Sengupta, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%